2014
DOI: 10.1017/s0033291714001998
|View full text |Cite
|
Sign up to set email alerts
|

Late preterm birth, post-term birth, and abnormal fetal growth as risk factors for severe mental disorders from early to late adulthood

Abstract: Although men born late preterm had an increased suicide risk, late preterm birth did not exert widespread effects on adult psychopathology. In contrast, the risks of severe mental disorders across adulthood were increased among individuals born SGA and individuals born post-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 102 publications
(169 reference statements)
4
65
2
Order By: Relevance
“…[Colour figure can be viewed at wileyonlinelibrary.com] Lahti et al did not find any association between late preterm birth (defined as week 34-36) and severe mental disorders in adulthood. 30 We only found a small increase in use of psychotropic medications overall in those born moderately preterm (defined as born in week 32-34) and late preterm (defined as born in week 35-36).…”
Section: Comparisons With Other Studiesmentioning
confidence: 64%
“…[Colour figure can be viewed at wileyonlinelibrary.com] Lahti et al did not find any association between late preterm birth (defined as week 34-36) and severe mental disorders in adulthood. 30 We only found a small increase in use of psychotropic medications overall in those born moderately preterm (defined as born in week 32-34) and late preterm (defined as born in week 35-36).…”
Section: Comparisons With Other Studiesmentioning
confidence: 64%
“…Riordan et al reported that younger maternal age and higher parity were similarly associated with suicide mortality, psychiatric admission and self‐harm, while low birthweight was associated with psychiatric admission, but not suicide mortality. In Lahti et al late preterm (a proxy for low birthweight) was associated with suicide in males, but not with severe psychiatric disorders requiring hospitalization or contributing to death. In our current research, low birthweight was not associated with any of the psychiatric disorders investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Insights into the mechanisms underlying the association of early‐life factors with later risk of suicide might be gained by establishing whether these specific factors are also linked to proximal psychiatric disorders (namely internalizing disorders, including depressive episode, and alcohol use disorder) and suicidal ideation that confer the highest risk for suicide . Very few studies have examined associations of early‐life factors with both suicide and psychiatric disorders and/or ideation/attempt , and those that are available are based on psychiatric admission.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few reports of increased risk of nonaffective psychosis and bipolar disorders in addition to depressive disorders. 10,11 Substance use disorders are reported in individuals born small for gestational age (SGA) 10,12 as opposed to those born preterm who are characterized as low risk takers. 13 Lower cognitive abilities and academic achievement are reported in low birth weight and/or preterm born adolescents and young adults, 4,13 as was also previously found in our project.…”
mentioning
confidence: 99%